DEVELOPMENT AND VALIDATION OF A GRADIENT PROGRAM RP-HPLC METHOD FOR ESTIMATION OF MULTIPLE ACTIVE PHARMACEUTICAL INGREDIENTS IN AN ORAL SUSPENSION TASTE MASKED WITH AN ION EXCHANGE RESIN - PANDIT, ROBINDRA K.; PANDEY, VIVEK (International Journal of Applied Pharmaceutics, 2025)
Objective: This study focuses on developing an effective Reverse Phase High-Performance Liquid Chromatography (RP-HPLC) method for the simultaneous analysis of Dextromethorphan Hydrobromide (DXM), Phenylephrine Hydrochloride (PEH), and Chlorpheniramine Maleate (CPM) in a taste-masked oral suspension. The method ensures rapid, precise, and accurate quantification of these Active Pharmaceutical Ingredients (APIs) while supporting formulation stability and regulatory compliance. Methods: A gradient High-Performance Liquid Chromatography (HPLC) method with a short 7.5-minute run time was optimized for the simultaneous analysis of DXM, PEH, and CPM in a complex suspension matrix. The taste masking was achieved using Indion 254 ion exchange resin, and its impact on drug release and assay accuracy was evaluated. Key method parameters, including resolution, plate count, and tailing factor, were optimized to ensure robust performance. The method was validated according to International Council for Harmonisation (ICH) guidelines, assessing specificity, precision, accuracy, and stability. Results: The developed DXM, PEH, and CPM method demonstrated excellent specificity, with no interference from the resin, excipients, or degradation products. Resolution values of more than 1.5 between ICH exceeded acceptance criteria, with plate counts more than 1500 and tailing factors within below 2. The method proved highly precise, with Relative Standard Deviation (RSD) values below 1%. It also ensured reliable quantification of Active Pharmaceutical Ingredients (APIs) in the presence of the taste-masking resin and under various stress conditions, confirming formulation stability. Conclusion: The developed HPLC method provides a rapid, precise, and reliable solution for analyzing APIs in a taste-masked oral suspension. Its efficiency and compliance with ICH guidelines make it a valuable tool for quality control, ensuring formulation consistency and patient safety.